Development Ischemic Stroke Model by Right Unilateral Common Carotid Artery Occlusion (RUCCAO) Method - Mentari, Ika Ayu; Naufalina, Rifda; Rahmadi, Mahardian; Khotib, Junaidi (Folia Medica Indonesiana, 2018)
This study was designed to examine motor and congnitive changes, infarct lesion and neurohistological changes, involving histologic staining and immunohistochemical expression of caspase-3 after induction by right unilateral common carotid artery occlusion (RUCCAO) for 90 minutes. The animals were divided into two groups: sham group and stroke model group. Cognitive impairment was evaluated by Y maze. Motor function was measured on days 0, 1, 3 and 7 using FUAT paradigm. Infarct area, histological and caspase-3 expressions were evaluated on day 14 after RUCCAO. The results showed that RUCCAO induced cognitive and motor impairment on day 3 and 7. Furthermore, stroke model group induced infarct lesion. Hispatology examination showed body damage of neuron cell in the ipsilateral hemisphere. Moreover, expression of caspase-3 on RUCCAO group was significantly higher than that in sham group. In conclusion, RUCCAO method caused significant cognitive and motor function impairment. Furthermore, RUCCAO also induced infarct lesions and cell death in the thalamus brain area. Thus, RUCCAO can be employed as a method for ischemic stroke model, especially in focal ischemia